NECESSITY OF PROPER EVALUATION IN EAP (ENGLISH FOR ACADEMIC PURPOSES) COURSES - Shihab, Md. Nuruddin Pier (Sanata Dharma University, Yogyakarta, 2025)
The paper shows the necessity of proper evaluation in EAP courses. It focuses on the roles of different stakeholders (learners, instructors, administrators) in evaluating EAP courses and settings, drawing on previously published articles. Further, it focuses on the impacts of evaluation on different stakeholders. This study emphasizes the positive impacts of proper evaluation and the negative impacts of improper evaluation, simultaneously considering the overall academic settings and organizational goals; to identify different variables; a rigorous analysis of the opinions of the participants is made. Besides, different spectacles are added in this paper by analyzing different literature and documents regarding EAP evaluation. Mainly, the focus of the paper is to show how the evaluation of EAP courses acts as a vital factor in academic contexts. As evaluation is one of the pillars of ESP, and proper evaluation can directly show the performances of the learners and instructors and can also show the viability of running a course or program in an academy, all the stakeholders, including administrators, need to remain careful to evaluate the other stakeholders properly and in a well-maintained academic manner. For this research, the qualitative descriptive method was employed. The analysis shows the impact of evaluation on different stakeholders of EAP courses.